How do food safety concerns affect consumer behaviors and diets in low- and middle-income countries? A systematic review - Liguori, Julia; Trübswasser, Ursula; Pradeilles, Rebecca; Le Port, Agnès; Landais, Edwige; Talsma, Elise F.; Lundy, Mark M.; Béné, Christophe; Bricas, Nicolas; Laar, Amos; Amiot, Marie Josèphe; Brouwer, Inge D.; et al. (Elsevier, 2022)
Both food safety and dietary behaviors are major contributors to the global burden of disease, especially in rapidly urbanising environments. The impact that food safety concerns have on dietary behaviors in low- and middle-income countries (LMICs) is insufficiently documented. Therefore, we examined whether food safety concerns influence consumer behaviors/diets in LMICs. A systematic review identified 46 relevant studies from 20 LMICs for inclusion. A socio-ecological food environment framework was used to map food safety factors that influence consumer behaviors (food acquisition/purchase, eating out of home, food preparation/storage) and diets (consumption of nutrient rich/poor foods). Several studies (n = 11) reported that despite food safety concerns, consumers could not always ensure that they consumed safe food; barriers were affordability, accessibility and appeal. Key concerns included fear of pesticides, fertilizers, hygiene in/around food outlets, unhygienic vendor practices and household storage/preparation methods. These concerns may reduce consumption of animal sourced food and fresh fruit and vegetables; and increase consumption of starchy staples and processed/packaged foods. Policies such as upgrading urban market infrastructure to enhance food safety, accompanied by nutrition and hygiene education, could lead to increased accessibility, affordability and appeal of safe, nutrient-rich foods. Thus, reducing the appeal of packaged/processed food as a means to mitigate food safety risk; thereby contributing to preventing foodborne disease and multiple forms of malnutrition.